Revision of the new world fauna of Mesembrina Meigen (Diptera: Muscidae) with the description of a new neotropical species - Kuchta, James S.; Savage, Jade (Zootaxa, 2008)
The large striking flies of the genus Mesembrina are typically found in boreal forest and at high elevations throughout the Northern Hemisphere. While it is known that most species are decomposers of ungulate dung, biological and taxonomic information on the New World fauna of Mesembrina is mostly out of date or unreliable. Consequently, the Nearctic taxa have been revised, resulting in the new synonymy of Mesembrina solitaria (Knab) with Mesembrina decipiens Loew, making M. decipiens the only species of the genus with a confirmed Holarctic distribution. Mesembrina latreillii Robineau-Desvoidy, contrary to previous indications, may be restricted to the Nearctic Region. The first Neotropical member of the genus, Mesembrina nigribasis sp. nov. is described. To place the New World fauna in context, a key to the world species of Mesembrina is provided. This key includes a species designated by Hennig as “resplendens subspecies” from the Palaearctic, which is a distinct but undescribed species.